Genre Specificity of Oral Histories about Starvation of 1941- 1945 - M. G. Matlin (Научный диалог, 2018)
The genre specificity of oral histories about starvation of 1941-1945 is covered. The review of the main works on the history of study of oral history in the national folklore is made. Consideration of the oral history as a speech genre allowed to establish that taking into account the peculiarities of oral speech helps to understand some of its properties in a new way, which, in turn, allows to rethink the traditional folkloristic approach to its analysis. It is shown that certain types of oral histories have a dual genre nature - on the one hand, they are speech genres, and on the other - folklore. The analysis of oral histories about starvation of 1941-1945 in the context of other works of reliable stereotypical prose, including those about fighting on the fronts of the Great Patriotic war, the blockade experience, the stay in captivity, led to the conclusion that a group of oral histories about starvation of 1941-1945 can be identified as a type of speech genre memories. It is shown that at the same time it is possible to define such stories as a folklore phenomenon representing a kind of a genre of the oral story devoted to the narration about a person in an extreme life situation.